2019
DOI: 10.1590/0037-8682-0347-2018
|View full text |Cite
|
Sign up to set email alerts
|

Emergence of chikungunya and Zika in a municipality endemic to dengue, Santa Luzia, MG, Brazil, 2015-2017

Abstract: Introduction: The recent circulation of arboviruses transmitted by vectors, such as dengue, chikungunya, and Zika, is concerning due to the high morbidity rates, clinical complications, and increased demand on health services. The objective of this study was to analyze the clinical and epidemiological aspects of an epidemic caused by arboviruses in the municipality of Santa Luzia, Minas Gerais, Brazil. Methods: Longitudinal study of patients with acute febrile disease and suspected arbovirus infection reported… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 34 publications
(33 reference statements)
0
6
0
Order By: Relevance
“…The symptoms of chikungunya are similar to those of dengue, typically in both of cases can notice pyrexia, myalgia, headache, and in some cases rash (Vega, et al, 2019). It mainly affects the peripheral joints, including wrists, knees, ankles, and additional symptoms of the disease include arthritis, tenosynovitis, rash and myalgia, especially in the lower back and leg muscles (Chen, et al, 2016).…”
Section: Diagnosismentioning
confidence: 99%
“…The symptoms of chikungunya are similar to those of dengue, typically in both of cases can notice pyrexia, myalgia, headache, and in some cases rash (Vega, et al, 2019). It mainly affects the peripheral joints, including wrists, knees, ankles, and additional symptoms of the disease include arthritis, tenosynovitis, rash and myalgia, especially in the lower back and leg muscles (Chen, et al, 2016).…”
Section: Diagnosismentioning
confidence: 99%
“…In MG, dengue and chikungunya had incidence rates of, respectively, 137 and 79.9 cases per 100,000 inhabitants in 2017, while Zika presented an incidence of 3.6 cases per 100,000 for the same period. In one of the few studies analysing the circulation of dengue, chikungunya and Zika in MG, with a focus on the city of Santa Luiza, Vega et al 16 , concluded that given the similarities in initial clinical profiles in order to differentiate these arboviruses it is necessary to perform detailed clinical evaluation, laboratory diagnosis and patient follow-up.…”
Section: Demographic Profilementioning
confidence: 99%
“…This scarcity is even more glaring when it comes to the analysis of the disease for the state of Minas Gerais (MG). Vega et al 16 have compared the emergence of chikungunya and Zika in the municipality of Santa Luzia, but there are no comprehensive studies of the disease's temporal and spatial distribution for the whole state, from the onset of the outbreak in 2015 until the present day.…”
Section: Introductionmentioning
confidence: 99%
“…Infectious and febrile diseases are transmitted by vectors and affect about 700,000 people who die each year in Brazil and worldwide [1,2], in Brazil febrile diseases such as dengue, Zika and Chikungunya are a concern for the public health system due to its increasing incidence in the last ten years [2].…”
Section: Introductionmentioning
confidence: 99%
“…Dengue, Zika and Chikungunya have shown a high morbidity rate in recent years [2], in clinical forms and with severe signs, has led the public health system to increase cases and the development of epidemic regions characterizing the co-circulation of DENV viruses, CHIKV and ZIKV. What has most concerned Brazilian researchers [8] is that 5% of symptomatic patients with dengue, Zika or Chikungunya may develop atypical manifestations such as neuropsychiatric [9] and these atypical manifestations in about a third of these patients are severe and are characterized by the need for support psychiatric [8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%